2012
DOI: 10.1080/02786826.2012.689118
|View full text |Cite
|
Sign up to set email alerts
|

Study of the PM Gas-Phase Filter Artifact Using a Setup for Mixing Diesel-Like Soot and Hydrocarbons

Abstract: The filter artifact is a significant source of error in gravimetric measurements of particulate matter (PM) exhaust. However, only a few studies on the subject exist. Results from these studies show a large discrepancy mainly because the experiments were performed using real diesel vehicle exhaust with varying exhaust composition. In this study, a setup for mixing diesel-like soot and hydrocarbon vapor was constructed for generating a stable exhaust aerosol with adjustable composition. The particle size distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Collection efficiency (CE) value represents the fraction of sampled particle mass that is detected by the detector and CE value is needed for the calculation of aerosol mass concentration measured by the AMS. Previous studies have shown that the CE of SP-AMS is affected by (i) particle losses during transit through the inlet and lens, (ii) the particle beam divergence for both tungsten and laser vaporizers and for tungsten vaporizer also due to (iii) bounce effects from the vaporizer (Huffman et al, 2009;Matthew et al, 2008;Onasch et al, 2012). It is known that in the standard AMS with only the tungsten vaporizer the CE can depend on the chemical composition and acidity of aerosol as well as sampling relative humidity (Middlebrook et al, 2012), the default value for the CE being 0.5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collection efficiency (CE) value represents the fraction of sampled particle mass that is detected by the detector and CE value is needed for the calculation of aerosol mass concentration measured by the AMS. Previous studies have shown that the CE of SP-AMS is affected by (i) particle losses during transit through the inlet and lens, (ii) the particle beam divergence for both tungsten and laser vaporizers and for tungsten vaporizer also due to (iii) bounce effects from the vaporizer (Huffman et al, 2009;Matthew et al, 2008;Onasch et al, 2012). It is known that in the standard AMS with only the tungsten vaporizer the CE can depend on the chemical composition and acidity of aerosol as well as sampling relative humidity (Middlebrook et al, 2012), the default value for the CE being 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…This technology development also has, in general, other effects than required by emission legislation; for example, fuel sulfur content limitations affect the emissions of nanoparticles. It should be noted that, e.g., semi-volatile compounds (e.g., low-volatility organics, sulfuric compounds) are not directly regulated even though they are partially detected in the gravimetric PM determination as P. Karjalainen et al: Time-resolved secondary particle formation from a gasoline car particles or adsorbed gas phase artefacts (Chase et al, 2004;Högström et al, 2012). Although not directly regulated, lowvolatility organics are likely to be affected by gaseous hydrocarbon limits.…”
Section: Introductionmentioning
confidence: 99%
“…Filter adsorption artifact is thought to be by either adhesion of organic gas molecules or adsorption of particle converted from gas onto the filter media. The contribution of mass by each mechanism is subject to multiple parameters such as filter face velocity, filter/ gas temperature, soot loading etc (Högström et al, 2012). Chase et al (2004) studied the effect of filter media and temperature on filter adsorption artifact for the measurement of vehicle PM emissions.…”
Section: Correlations Between the Metricsmentioning
confidence: 99%
“…Previous studies have only focused on improving the thermal efficiency or fuel economy of the heaters [6]. Conversely, AHs have also been used as artificial soot generators in laboratories after modifying their combustion parameters [7], which do not represent normal use emissions.…”
Section: Introductionmentioning
confidence: 99%